2012
DOI: 10.5688/ajpe769170
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Valued by the Pharmacy Practice Community When Hiring a Recently Graduated Pharmacist

Abstract: Objective. To determine those characteristics that are most valued by members of the pharmacy practice community when hiring a new pharmacist. Methods. A survey instrument describing 20 characteristics that a pharmacy graduate may possess was created and sent to pharmacists licensed in Colorado. Respondents were asked to select and prioritize the top 5 characteristics considered most important in hiring a new graduate pharmacist. Responses were segregated by practice (retail vs. institutional) and/or by pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 9 publications
1
22
1
Order By: Relevance
“…These results are consistent with the findings that of emphasized professionalism and communication skills as pivotal for hiring practices. [1,3] Similar to the findings in the current study, Henderson (2012) asserted that student clinical experience serves as a viable resource for future employment. [8] In his study, Henderson reported than an increased minority workforce was attractive to future employers and, in an effort to foster entry of minorities into healthcare careers, the benefits of internships for minority students was examined.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…These results are consistent with the findings that of emphasized professionalism and communication skills as pivotal for hiring practices. [1,3] Similar to the findings in the current study, Henderson (2012) asserted that student clinical experience serves as a viable resource for future employment. [8] In his study, Henderson reported than an increased minority workforce was attractive to future employers and, in an effort to foster entry of minorities into healthcare careers, the benefits of internships for minority students was examined.…”
Section: Discussionsupporting
confidence: 67%
“…In a similar study of pharmacy graduates strong communication and professional behavior were highly regarded by pharmacists when hiring pharmacy graduates. [3] Studies have evaluated possible benefits to the institution when a graduate is hired that had completed a clinical experience at that institution. In particular, it has been proposed that this practice may help to address the deleterious consequences of the staffing shortages.…”
Section: Introductionmentioning
confidence: 99%
“…Thompson and colleagues surveyed practicing pharmacists in both community and health system settings, asking them to rank which characteristics were most essential when considering hiring a newly graduated pharmacist [6]. Of the 20 characteristics listed for prioritization, communication was ranked as the highest preferred characteristic a graduate could possess across all settings, with professionalism ranking second.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search was done to identify common characteristics valued by pharmacy employers and residency or postdoctoral programs. 15,16,17,18 Skill categories were constructed from this information, then vetted and refined based on feedback from a select group of clinical pharmacy faculty from private and public universities. These skill categories and characteristics were listed in the self-evaluation section for pharmacy students to identify as strengths or weaknesses.…”
Section: Methodsmentioning
confidence: 99%